AJARAN BHATARA KUMARA DALAM TUTUR KUMARA TATWA DAN PENGARUH TERHADAP KEHIDUPAN MANUSIA - Artayasa, I Wayan (Kalangwan Jurnal Pendidikan Agama, Bahasa dan Sastra, 2021)
Hindus considered Bhatara Kumara in Bali as a protector or guardian deity for newborn children. Offering and worshiping Bhatara Kumara is very important to do every day to protect or give children gifts. However, in Tutur Kumara Tatwa, Bhatara Kumara teachings are not only for children but for all people. The teachings conveyed are a form of self-control in this life. The teaching or education in Tutur Kumara Tatwa certainly has implications for human life, especially in Bali. Children's education is essential to do from an early age to develop good character. Good character is not only for children but also applies to all human beings. According to Tutur Kumara Tatwa, character education from Bhatara Siwa to Bhatara Kumara originated from a field where Bhatara Kumara was grazing called Argakuruksana. Bhatara Kumara felt like life in solitude. During his life as a shepherd, he had experienced many ups and downs. It is what can be learned as teaching or values in life that can affect human life. Bhatara Kumara was blessed or awarded by Bhatara Shiva to stay young, achieving eternal happiness. Bhatara Kumara is represented as the god of a baby. It means that babies should have received character education from their parents. Bhatara Kumara's role in human life, especially for Bali's Hindu community, is seen as the God of children from birth to Telung Oton's age (630 days). Bhatara Kumara is placed in Pelangkiran and is believed to be the child's protector or guardian